A contribution to the knowledge of the orientai Chrysomelidae: two new species of Eumolpinae with description of a new genus (Coleoptera) (Bollettino di zoologia agraria e bachicoltura, 2024)
Colaspedusa verrucosa n. sp. is described from Thailand (Suratthani Prov., Khao Sok Nat. Park) and compared with the only other species known for the genus (C. bicoloripes Medvedev), of which a picture of the habitus and the description of the spermatheca are provided. Pseudolepis n. gen. is described for P. squamosa n. sp. from Malaysia (vie. of Kuala Lumpur); the new genus belongsto the tribe Adoxini and is strictly related to Aulacolepis Baly to which is compared.